Shock wave dynamics in nanoporous tungsten and molybdenum via molecular dynamics simulations: Insights into thermodynamic and structural evolution - Yiqun Hu; Zhenhai Li; Xiumin Xu; Yuhang Zhang; Re Xia (Journal of Materials Research and Technology)
Nanoporous tungsten (NP–W) and molybdenum (NP–Mo) are of great interest in aerospace and nuclear fusion/fission reactor industrial sections. Molecular dynamics (MD) simulations are employed for understanding the influences of shock velocity and relative density on the shock responses of NP-W and NP-Mo with stochastic bicontinuous structural features. Thermodynamic simulations reveal that temperature changes exhibit relatively low sensitivity to variations in relative density for a given shock velocity. Conversely, pressure and shock wave velocity increase substantially with rising relative density. NP-W specimen demonstrates higher shock-induced pressures and temperatures compared to NP-Mo. The porous structure exhibits greater susceptibility to heat generation under shock loading than the bulk. Hugoniot relations reveal that the wave velocity of NP-Mo is slightly greater than that of NP-W. NP-Mo exhibits greater resistance to amorphization than NP-W at shock velocities below 2.0 km/s. Specifically, at up = 1.5 km/s and t = 50 ps, the amorphous conversion percentages of BCC atoms in NP-W/NP-Mo are 49.6%/47.0% (φ = 0.40), 58.5%/52.2% (φ = 0.50), and 68.1%/57.5% (φ = 0.60), respectively. This investigation provides a fundamental understanding of shock wave behavior exhibited by nanoporous refractory metals at atomic scales and will provide precious theoretical and design guidelines for potential industrial applications.